Perluasan Tafsir Frasa Tahap Penyelidikan melalui Interprestasi Sistematis sebagai Solusi Perselisihan Prayudisial - Suwitno Yutye Imran; Abdul Madjid; Apripari Apripari (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
This study examined two things; the first is related to the relationship between judicial disputes, legal protection, and the role of the preliminary investigator; the second is related to the expansion of the phrase of preliminary investigation stages in the Criminal Procedure Code through systematic interpretation. This study applied normative legal research methods specified on the type of legal research for in-concreto cases. To strengthen the study, a statutory approach, a case approach, and a theoretical approach were used. The results of the study found that the actions of preliminary investigator who were limited to carrying out preliminary investigation without paying attention to cases that had a direct relationship with the cases being investigated could not yet provide legal protection, because they opened up opportunities for judicial disputes to occur. Speaking of which, judicial disputes need to be avoided through the use of systematic interpretation carried out by preliminary investigator in the preliminary investigation stages to expand the interpretation of the phrase of preliminary investigation stages in the Criminal Procedure Code and its derivative regulations. The systematic interpretation referred to is carried out in a limited manner, by simply reading opportunities for civil lawsuits and state administrative requests from parties involved in the case being investigated. In addition, it ensured the similarity of the parties involved in criminal cases as well as civil cases or state administrative cases in question.